Gonadal Cycle-Dependent Expression of Genes Encoding Peptide-, Growth Factor-, and Orphan G-Protein-Coupled Receptors in Gonadotropin- Releasing Hormone Neurons of Mice - Vastagh, Csaba; Csillag, Veronika; Solymosi, Norbert; Farkas, Imre; Liposits, Zsolt (Frontiers in Molecular Neuroscience, 2021)
Rising serum estradiol triggers the surge release of gonadotropin-releasing hormone (GnRH) at late proestrus leading to ovulation. We hypothesized that proestrus evokes alterations in peptidergic signaling onto GnRH neurons inducing a differential expression of neuropeptide-, growth factor- and orphan G-protein-coupled receptor genes. Thus, we analyzed the transcriptome of GnRH neurons collected from intact, proestrous and metestrous GnRH-GFP transgenic mice using Affimetrix microarray technique. Proestrus resulted in a differential expression of genes coding for peptide/neuropeptide receptors including Adipor1, Prokr1, Ednrb, Rtn4r, Nmbr, Acvr2b, Sctr, Npr3, Nmur1, Mc3r, Cckbr and Amhr2. In this gene cluster, Adipor1 1 mRNA expression was up-, the others were down-regulated. Expression of growth factor receptors and their related proteins was also altered showing upregulation of Fgfr1, Igf1r, Grb2, Grb10 and Ngfrap1 and downregulation of Egfr and Tgfbr2 genes. Gpr107, an orphan G protein-coupled receptor (GPCR) was upregulated during proestrus, while others were significantly downregulated (Gpr1, Gpr87, Gpr18, Gpr62, Gpr125, Gpr183, Gpr4, Gpr88). Further affected receptors included vomeronasal receptors (Vmn1r172, Vmn2r-ps54, Vmn1r148) and platelet-activating factor receptor (Ptafr), all with marked downregulation. Patch-clamp recordings from mouse GnRH-GFP neurons carried out at metestrous confirmed that the differentially expressed IGF-1-, secretin- and GPR 107 receptors were operational as their activation by specific ligands evoked an increase in the frequency of miniature postsynaptic currents (mPSCs). These findings show the contribution of certain novel peptides, growth factors and ligands of orphan GPCRs to regulation of GnRH neurons and their preparation for the surge release.